Slovenščina v visokem šolstvu: sploh sme biti vprašanje ubesediti in opredeliti po slovensko? - Žele, Andreja (Slavia Centralis, 2020)
Slovenian in higher Education: Need this be treated as a question?The paper presents and deliberates on the current state of Slovenian as the language of instruction at national universities as well as its status as the language of science. Technical Slovenian straightforwardly confirms that language is the expression of our own conceptualized thought, i.e., the nation’s own mental capability. The development of technical Slovenian depends upon regular academic publications and high-standard textbooks in which Slovenian terminology is clearly defined and presented; this paper reviews the status of all recounted points.
Keywords: Slovenian language; language of instruction; Slovenian university; highigher education textbooks; technical Slovenian